Automotive and Engine Technology The International Journal of WKM - Eckstein, Lutz.; Eichlseder, Helmut; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
This journal is the official academic organ of WKM, The Scientific Society for Automotive and Engine Technology. Its focus is on the latest R&D findings on every aspect of passenger car and commercial vehicle engineering on the one hand, and engine development and technology on the other hand. Expert authors from science and industry report on individual research projects as well as on latest development of vehicles, their engines and other components. This journal provides in-depth technical articles that give an exclusive insight into progress in automotive engineering and engine technology, constituting an essential source of information for all automotive engineers worldwide.
Keywords: Automotive engineering; Engines; Transportation engineering; Traffic engineering; Automotive Engineering; Engine Technology; Transportation Technology and Traffic Engineering